Evaluation of a human glycated hemoglobin test in canine diabetes mellitus. (May 2019) - Kim, Na-Yon; An, Jaehoon; Jeong, Jae-Kyung; Ji, Sumin; Hwang, Sung-Hyun; Lee, Hong-Seok; Kim, Myung-Chul; Kim, Hyun-Wook; Won, Sungho; Kim, Yongbaek
Glycated hemoglobin A1c (HbA1c) is widely used for monitoring and diagnosing human diabetes mellitus, but is rarely used in veterinary clinics. The goal of our study was to validate the commercial HbA1c testing system SD A1cCare analyzer (Bionote, Gyeoggi-do, South Korea) for use in dogs. Dogs were recruited with owner's consent. Diabetic status was determined based on clinical signs, fasting hyperglycemia, and glycosuria. Intra-assay precision and linearity were evaluated with EDTA, heparin, or citrate as anticoagulants, and had excellent precision with mean coefficients of variation (CVs) of 2.47%, 2.26%, and 1.92%, respectively. Diluted anticoagulated blood samples showed excellent linear relationships with R 2 of 0.991, 0.996, and 0.994, respectively. Inter-assay precision revealed that the mean CV of the normal control was 2.18% and that of the high control was 2.01% (30 repeats). Observed total error of a normal control was 7.81%, and 6.12% for the high control. HbA1c level measured before and after removal of plasma and replacement by saline showed minimal interference by lipid contents ( p = 0.929). The HbA1c concentrations of diabetic dogs were significantly higher than those of non-diabetic dogs ( p < 0.001). HbA1c value >6.2% indicated canine diabetes through a classification and regression tree model. In most cases, fructosamine and HbA1c were highly correlated ( r = 0.674, p < 0.001). The HbA1c testing system could be a valuable testing system to evaluate canine diabetes mellitus, providing an alternative in-house option for use by veterinary clinicians.